Effect of Curing Temperature, Activator Solution Composition and Particle Size in Brazilian Fly-Ash Based Geopolymer Production - Azevedo,Adriano Galvão Souza (2019)
The geopolymer binder is a relatively new class of inorganic binding material of elevated mechanical strength and good chemical properties. This can be produced using clay minerals or byproducts of the industrial processes, such as metakaolin, fly-ash and blast furnace slag. In this work, geopolymers were produced by alkaline activation of a Brazilian fly-ash with simple and compound solutions (NaOH and NaOH + Na2SiO3). The hardened specimens presented values of the mechanical strength close to 48 MPa when the activator used presented SiO2/Na2O ration close to 1.0 after 24 h of curing at 65 ºC. The increase of the temperature to 90 ºC favored the reactions of the N-A-S-H gel (geopolymer) formation and compression strength increased to values close to 90 MPa after 24 h. It has been found that physical properties, such as density and porosity, varied when different SiO2/Na2O rations was present in alkaline solutions. Time, temperature of curing and particle size of fly-ash modified the mechanical and physical proprieties of hardened inorganic binder. Was observed the diffraction phases related to zeolitic phases and carbonate new bands of absorption were related to reactions of Na2O in excess with atmospheric CO2. The variation of SiO2/Na2O modified the microstructural of the hardened specimens.